Getting enamels on the basis of recycled polystyrene - Шолух, Наталія Євгенівна (Eastern-European Journal of Enterprise Technologies, 2014)
The formulations for lacquer and enamel compositions based on "secondary" polystyrene were developed, and physicomechanical properties of coatings based on these compositions were studied. It was shown that as a solvent, it is better to use a mixture of toluene and ethyl acetate in the ratio of 1:1 that allows obtaining lacquer compositions with high speed of drying out and time, sufficient for forming a heavy-duty coating. It was determined that the physicomechanical characteristics of all samples of paint compositions are higher comparing to the known similar enamels (TU 67-371-81 Enamels polystyrene), namely coating hardness and water resistance characteristics. Using "secondary" polystyrene in the developed compositions will significantly reduce lacquer and enamel costs. Using polystyrene wastes for the production of lacquers and enamels will solve two urgent problems: the saving of crude products and materials, involved in the production of polymeric materials and the environmental protection of industrial regions.